Pemanfaatan Buah Ciplukan Menjadi Lip Balm Yang Bernilai Jual - Vionita, Deviyani; Haryati, Eka; Afifah, Jihan; Rahmah, Salsabila; Arozaq, Desfi Liqel; Susanti, Eka Nana (Universitas Hamzanwadi, 2024)
Ciplukan fruit (Physalis angulata L.) has potential as a raw material for making natural lip balm. The content of phytochemical compounds such as vitamin C, flavonoids, alkaloids, steroids and carotenoids makes ciplukan useful as an anti-inflammatory and increasing skin antioxidant production. Ciplukan extraction can be used for skin treatment and as a cosmetic for sensitive skin. This research method uses the orgaleptic test, Ph test, and homogeneity test including the stages of preparation, production, marketing, goal achievement, evaluation, and reporting. The results of this research are that the manufacture of ciplukan fruit extract lip balm has met the requirements of the orgaleptic test, the pH test with a pH level of 5, and homogeneity where the lip balm product is homogeneous. This research proves that ciplukan fruit extract can be applied in making natural lip balm that is effective and popular with consumers. Online marketing and participation in entrepreneurial events have succeeded in increasing product sales. Therefore, the formulation of lip balm from ciplukan fruit extract has the potential to be further developed as an environmentally friendly and beneficial skin care product.